1999
DOI: 10.1021/om990745h
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-Catalyzed Acrylonitrile Hydrophosphination. P−C Bond Formation via Olefin Insertion into a Pt−P Bond

Abstract: The acrylonitrile complexes Pt(diphos)(CH 2 CHCN) (diphos ) dppe (1), dcpe (2); dppe ) Ph 2 PCH 2 CH 2 PPh 2 , dcpe ) Cy 2 PCH 2 CH 2 PCy 2 , Cy ) cyclo-C 6 H 11 ) are catalyst precursors and, for some substrates, resting states, during addition of P-H bonds in primary and secondary phosphines across the CdC double bond of acrylonitrile (hydrophosphination). Oxidative addition of P-H bonds to related catalyst precursors gives the phosphido hydride complexes Pt(diphosAcrylonitrile does not insert into the Pt-H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(49 citation statements)
references
References 45 publications
2
46
0
1
Order By: Relevance
“…The methyl ligand possess a Pt-C(3) = 2.129(4) Å, which is longer than Pt-C(3) = 2.083(3) Å of 6, but not atypical of platinum methyl species [42]. The highly analogous platinum phosphide Pt(dcpe)(CH 2 CH 2 CN)(PHMes ⁄ ) (dcpe = 1,2 bis(dicyclohexylphosphino)ethane) reported by Glueck and coworkers has a Pt-P = 2.390(2) Å which is quite similar to Pt-P(3) = 2.386(1) Å observed for 11 [50]. Chloride-substituted platinum phosphides 9 and 10 have nearly the same platinumphosphorus bond lengths Pt-P(3) = 2.3910(9) Å and Pt-P(3) = 2.396 (2) [12][B(C 6 F 5 ) 4 ]) as translucent crystals in 87% and 85% isolated yield, respectively (Scheme 2).…”
Section: ð4þsupporting
confidence: 52%
“…The methyl ligand possess a Pt-C(3) = 2.129(4) Å, which is longer than Pt-C(3) = 2.083(3) Å of 6, but not atypical of platinum methyl species [42]. The highly analogous platinum phosphide Pt(dcpe)(CH 2 CH 2 CN)(PHMes ⁄ ) (dcpe = 1,2 bis(dicyclohexylphosphino)ethane) reported by Glueck and coworkers has a Pt-P = 2.390(2) Å which is quite similar to Pt-P(3) = 2.386(1) Å observed for 11 [50]. Chloride-substituted platinum phosphides 9 and 10 have nearly the same platinumphosphorus bond lengths Pt-P(3) = 2.3910(9) Å and Pt-P(3) = 2.396 (2) [12][B(C 6 F 5 ) 4 ]) as translucent crystals in 87% and 85% isolated yield, respectively (Scheme 2).…”
Section: ð4þsupporting
confidence: 52%
“…(26)]. [97,98] Phosphines were shown to Originally, a mechanism analogous to Scheme 3 was proposed, in which the initial PÀH oxidative addition to Pt 0 is followed by a regioselective alkene insertion into the PtÀP bond, and subsequent CÀH reductive elimination releases the product to complete the catalytic cycle.…”
Section: Oxygen Nucleophiles: Platinum-catalyzed Epoxidation Of Alkenesmentioning
confidence: 99%
“…On the other examples, the mechanism of the hydrophosphination was extensively investigated by Glueck et al [59][60][61][62]. To exclude the alternative possibility of catalysis by binuclear complexes [57,5] complexes of 2 -coordinated acrylonitrile and bidentate phosphine ligands (diphos) were used as precatalysts [59].…”
Section: Addition Of P-h Phosphines To Cyano Substituted Olefins (Hydmentioning
confidence: 99%
“…Assuming that the insertion of acrylonitrile into the Pt-P bond in phosphido-hydride complexes proceeds regioselectively, the authors suggested that using of a chiral precatalyst could give rise to a enantiomerically enriched tertiary phosphine [60]. To examine this possibility the investigation of the stereochemical aspect of the acrylonitrile insertion into phosphido-hydride complexes was performed followed by 31 P NMR.…”
Section: Addition Of P-h Phosphines To Cyano Substituted Olefins (Hydmentioning
confidence: 99%